1974
DOI: 10.1002/1097-0142(197409)34:3<554::aid-cncr2820340313>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Lobular carcinoma in situ of the breast(Long-term followup

Abstract: Ninety‐eight women with lobular carcinoma in situ (LICS) of the breast were identified over a 16‐year period. Consecutive slide review of all breast material over a 12‐year period identified 25 women with LCIS on biopsy who did not undergo mastectomy. Only 1 woman (4%) in a complete followup averaging 17.5 years developed ipsilateral invasive carcinoma. of 32 women with a contralateral breast at risk, 3 (9.7%) developed infiltrating carcinoma. LCIS was found with infiltrating carcinoma, especially of the lobul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
72
0
5

Year Published

1975
1975
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(80 citation statements)
references
References 14 publications
3
72
0
5
Order By: Relevance
“…1,18 They occur predominantly in premenopausal women, with most cases being diagnosed in women between 40 and 50 years of age. 13,[19][20][21][22] They are clinically occult, and although they are often also mammographically silent, a significant minority of lobular neoplasia cases diagnosed on core biopsy have associated microcalcifications. [23][24][25][26] Data derived from the Surveillance, Epidemiology and End Results Program 27 have shown that the ageadjusted, age-specific rates of LCIS among women in the United States has increased fourfold between the late 70s (0.9 per 100 000 person years) and late 90s (3.2 per 100 000 person years).…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…1,18 They occur predominantly in premenopausal women, with most cases being diagnosed in women between 40 and 50 years of age. 13,[19][20][21][22] They are clinically occult, and although they are often also mammographically silent, a significant minority of lobular neoplasia cases diagnosed on core biopsy have associated microcalcifications. [23][24][25][26] Data derived from the Surveillance, Epidemiology and End Results Program 27 have shown that the ageadjusted, age-specific rates of LCIS among women in the United States has increased fourfold between the late 70s (0.9 per 100 000 person years) and late 90s (3.2 per 100 000 person years).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…11,29,30 LCIS confers B15% absolute risk of developing breast cancer at 15 years, but a significant number of subsequent carcinomas occur more than 15 years after a diagnosis of LCIS. 2,12,[19][20][21] Although lobular neoplasia has been linked to an increased risk of subsequent carcinoma in either breast, 12,13,21 several studies have shown a higher, although not always statistically significant, risk in the ipsilateral breast. 3,14,17,20,30,31 Cancer risk in ALH seems to vary with patient age; an initial diagnosis of ALH in postmenopausal women has been associated with a lower risk of subsequent carcinoma development than in premenopausal women.…”
Section: Epidemiologymentioning
confidence: 99%
“…However, later studies have shown an association between classic types and increased bilateral cancer risk, and therefore these lesions have since been regarded as a risk marker rather than a true precursor. 1,[3][4][5] Because of the recognition of indolent lesions as portending increased cancer risk, many favor the terminology of LN and LIN over the anxiety-producing word carcinoma used in the designation of LCIS (written communication with Kathleen Diehl, MD, member of The Consensus Committee of the American Society of Breast Disease, April 23, 2014). Use of the broader diagnosis of LN also reduces subjectivity related to intraobserver and interobserver variability in distinguishing ALH and LCIS.…”
mentioning
confidence: 99%
“…1 LCIS is typically multicentric and bilateral and has no specific clinical manifestation or radiologic features. [2][3][4] LCIS is usually identified as an incidental pathology finding outside the area of abnormality which prompts a biopsy of the breast. Therefore, the true incidence of LCIS in the general population is unknown.…”
mentioning
confidence: 99%
“…Approximately 50% of subsequent breast malignancies occur more than 15 years after LCIS was diagnosed. [2][3][4] There are conflicting reports regarding the type of cancer diagnosed after LCIS, specifically the percentage of invasive lobular carcinoma (ILC), which ranges from 50 -70% of invasive tumors in different series. 2-4,9 -12 The percentage of ILC rises when the original diagnosis of LCIS was made according to rigid criteria.…”
mentioning
confidence: 99%